(untitled) (Research, Society and Development, 2022)
The eco-efficiency index must be measured based on environmental, energy and material parameters, among others, where it will help in the fight against waste and should contribute to monitoring the implementation of a sustainable project. In this work, an algorithm based on the AHP method was developed aiming to help people in decision-making in projects that simulate real combustion situations; the MATLAB software was used for this. The steps used were: Definition of criteria (SOx, NOx, PM, and VOC emissions), creation of the judgment matrix, and simulation of the values assigned to the projects (using CONAMA resolution 436/2011 as a parameter). The results showed that project 3 had the best eco-efficiency index since its decision vector has the lowest impact compared to other projects; likewise, project 2 proved to be the most harmful under the conditions evaluated. It is expected that from this work new more complex solutions can be created using new criteria, scenarios, and other methods and programming logic.